Characterization of the interactions of β‒amyloid peptides with glycolipid receptors by surface plasmon resonance. Issue 2 (2003) - Valdes‒Gonzalez Valdes‒Gonzalez, Tania Tania; Inagawa Inagawa, Junichi Junichi; Ido Ido, Tatsuo Tatsuo
Abstract : Interactions between β ‒amyloid (A β ) peptides and neuronal membranes play an important role in Alzheimer's disease (AD). Using surface plasmon resonance we assayed a kinetic model to study the interactions of A β 25‒35, A β 40 and A β 42 with surfaces containing single glycolipids (Asialo‒GM1, GM1, GD1a or GT1b). The larger peptides interacted with gangliosides stronger than A β 25‒35, which showed some significant bindings solely at high concentrations under acidic conditions. Only the interactions at low A β concentrations were useful to calculate the kinetic constants. The affinities increased at low pH. The specificity, but not the affinity correlated with the number of sialic acids in the ganglioside sugar moiety. The most important finding in this study, was a special group of sensorgrams with linear association phases that appeared for the interactions of A β with the membranes containing gangliosides, due to the following process: when A β is injected at a critical concentration, the first molecules that interact with the gangliosides remain fixed on the membrane. Next A β molecules bind to these fixed molecules, so that for each A β molecule bound, new binding sites are activated on the surface in a linear ratio, which explains the linear shape of the sensorgrams. This way a laminar‒arranged A β accumulate is progressively formed on the membrane surface and fixed there. These linear sensorgrams were not observe with asialo‒GM1 or DMPC, which indicates the main role of sialic acid in these interactions. This model for progressive A β deposition could simulate the initial stage of the A β peptide accumulation on cell surfaces.